The production of radiopharmaceuticals at the Isotope Center - Jorge Cruz Arencibia (Nucleus, 2014)
Next to the 20th anniversary of its creation, the Isotope Centre consolidates its results as one of the pillars of nuclear power sustainability in the country. It includes a brief review of the centre’s current status in radiopharmacy and its main challenges that, from our perspective, the mentioned institution shall face.